2007
DOI: 10.1111/j.1743-6109.2007.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an Anabolic Steroid Changes Female Mice's Sexual Responses According to Sex Partner

Abstract: Introduction Anabolic androgenic steroids (AAS) affect human female sexual behaviors. Animal models have been useful in uncovering the neural mechanisms governing changes in female sexual response upon AAS exposure. Aim We quantify the sexual response of AAS-exposed gonadally intact female mice when paired with gonadally intact female or male pairs. Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In this study, we suggested existence of ultimate strategy based on the hierarchical disparity. Recent authors focused on brain reaction [51][52][53][54] and hormonal levels [55,56] to elucidate proximate mechanisms connected to sexual arousal. For example, Sagarin et al [57] reported increased salivary testosterone level in women who engaged in SM interaction in submissive positions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we suggested existence of ultimate strategy based on the hierarchical disparity. Recent authors focused on brain reaction [51][52][53][54] and hormonal levels [55,56] to elucidate proximate mechanisms connected to sexual arousal. For example, Sagarin et al [57] reported increased salivary testosterone level in women who engaged in SM interaction in submissive positions.…”
Section: Discussionmentioning
confidence: 99%
“…To this date, it is yet unclear whether prenatal, postnatal, or perinatal androgen environments play a role, if any, in establishing gender identity. However, it is becoming increasingly clear that androgens play a strong modulatory role on adult female sexual behaviors [36–38]. Nevertheless, the precise mechanism(s) underlying gender identity formation in children is/are unknown ([10]; for a review, see [26]).…”
Section: Discussionmentioning
confidence: 99%